The Parkinson’s disease-associated genes ATP13A2 and SYT11 regulate autophagy via a common pathway - Carla F. Bento (Nature Portfolio, 2016)
Mutations in ATP13A2 are associated with lysosomal dysfunction and early onset Parkinson’s disease. Here Bento et al. show that ATP13A2 depletion negatively regulates SYT11, at both transcriptional and post-translational levels, which in turn impairs function of the autophagy-lysosome pathway.